Synthesis and Characterization of First Row Metal Complexes Derived from a Pyridinophane Ligand Functionalized by Fluoroalcohol. Issue 8 (22nd March 2017) - Guillo, Pascal; Daran, Jean‐Claude; Manoury, Eric; Poli, Rinaldo
Abstract: A new tetradentate N‐donor ligand (L ) based on 2, 11‐diaza[3.3](2, 6)pyridinophane with N‐bonded (CF3 )2 (OH)CCH2 groups is presented, along with the coordination compounds [(L )FeCl2 ][FeCl4 ], [(L )MnCl2 ], [(L )Cu(OAc)2 ] and [(L )Zn(OTf)(H2 O)](OTf) (OAc=acetate; OTf=trifluomethylsulfonate). All metal complexes possess a distorted octahedral geometry around the metal center. Abstract : Fluoraoalcohol groups have been introduced on a tetradentate N‐donor ligand. Four metal complexes containing this ligand are described.